Fraud Triangle Analysis in Detecting Fraudulent Financial Statement: Meta-Analysis - Adinata, Restu Eri; Wuryani, Eni; Triani, Ni Nyoman Alit (Jurnal Pendidikan Akuntansi (JPAK), 2025)
This study aims to examine the effect of fraud triangle in detecting financial statement fraud. The fraud triangle has several factors that influence the occurrence of fraud, namely Pressure, Opportunity, and Rationalization. In this study, Pressure is proxied with Financial Stability, External Pressure, Personal Financial Need, Financial Targets. While Opportunity is proxied through Nature of Industry and Ineffective Monitoring. Meta-analysis techniques were used in this study to seek conclusions about similar individual research trends. The sample of this study amounted to 20 articles which were further carried out quantitative analysis. The results of the meta analysis show that Financial Stability, Nature of Industry, Ineffective Monitoring, and Rationalization have a positive influence on financial statement fraud. While External Pressure, Personal Financial Need, and Financial Targets has a negative influence on financial statement fraud. These results show that the three factors studied do not support financial statement fraud committed by the company. This can happen because of differences in measurement proxies in measuring variables